(untitled) (Research, Society and Development, 2021)
The progression of confirmed cases of Covid-19 in Brazil has also been influenced by socioeconomic factors, in addition to the contagion dynamics typical of an epidemic. For this reason, the updated analysis of the epidemiological distribution of Covid-19 by municipalities is of paramount importance, as well as relating it to socioeconomic development, using the Municipal Human Development Index (IDHM) as an indicator. Thus, the main objective of this work was to analyze the epidemiological distribution of Covid-19 and its relationship with the IDHM of the municipalities of Pará. This is an ecological, exploratory, and analytical study. The incidence of Covid-19 of the 144 municipalities in Pará was analyzed, and these data were collected in the database of the Public Health Department of the Government of Pará. by Covid-19, from March 2020 to April 2021. A Pearson correlation analysis was performed, based on incidence x IDHM data. It was possible to observe that the occurrence of the Covid-19 incidence coefficient was more pronounced in two microregions of Pará: Belém and Parauapebas. However, it was not possible to conclude that this higher incidence is linked to the higher incident population in these regions. Socioeconomic conditions, represented by the IDHM, did not show strong correlation with the epidemiological variables of Covid-19, apart from the Belém microregion.